Cooperation programs regarding the development of turnover in rural area - Daniela Ileana Godja (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
This paper aims to analyze the data regarding the cooperation programs supporting the development of agrotourism of Romania. The data were taken from the Ministry of Agriculture and Rural Development and were processed according to the objectives of the paper, namely the allocation of European funds for the period 2007-2013 for Measure 3.1.3. - Encouraging tourism activities. To achieve this it was necessary to analyze the projects submitted, the projects selected and contracted. The aim of the paper is to develop tourism activities in rural areas that will help to increase the number of jobs and alternative incomes, as well as to increase the attractiveness of the rural area. This measure aimed at investing in rural areas, namely: investing in infrastructure in areas with tourism potential, investing in recreational activities, investing in infrastructure, investing in information centers, investing in tourist marking development, development and marketing of tourist services as a part an integral part of rural tourism.
Keywords: O11; Q13; 330; agritourism; cooperation programs; investments